Dietary Pattern, Nutrient Intake, and Perceived Fatigue in the Oldest Old (P18-027-19). (13th June 2019) - Liu, Yi-Hsuan; Gao, Xiang; Mitchell, Diane; Wood, Craig; Still, Christopher; Jensen, Gordon
Abstract: Objectives: Little is known regarding dietary patterns and diet composition for the oldest old (defined as adults ≥ 80 years old) who usually have compromised diet quality due to age-related decline. We examined overall dietary patterns and further related the patterns to consumption of selected nutrients as well as perceived physical and mental fatigue. We hypothesized that those that had a healthy dietary pattern would have better nutrient intake profiles and reduced perceived fatigue. Methods: We studied a cross-section of the Geisinger Rural Aging Study (GRAS) longitudinal cohort in rural Pennsylvania that included 122 participants (56 men and 66 women) aged from 82 to 97 years old. Average daily nutrient and food group intake were calculated from the average of three dietary recalls (1 weekend and 2 weekdays) by telephone. Dietary patterns were characterized using cluster analysis of 34 food groups. Mean nutrient intake and standard errors across dietary patterns were calculated after adjusting for age, sex, and energy consumption. Mean Pittsburgh fatigability questionnaire score examining physical and mental fatigue were calculated after adjusting for age, sex, and body mass index. Results: Two dietary patterns were defined: one pattern ( n = 53) characterized by its higher consumption of fruits, vegetables, seafood, and whole grains, and another pattern ( n = 69), with higher intake of fats and oil, refined grains, and cheese. After adjusting for potential confounders, participants in the healthier pattern had significantly higher consumption of carbohydrate, protein, fiber, vitamin A, E, K, C, B6, B12, iron, zinc, and potassium with lower intakes of fat and sodium compared with those in the less healthy pattern ( P < 0.05 for all). Participants in the healthier pattern had a higher Healthy Eating Index-2015 score (adjusted mean: 70.6 vs 51.8; P < 0.001) and a lower physical fatigue score (adjusted mean: 17.6 vs 21.9) and mental fatigue score (adjusted mean: 6.77 vs 11.6) relative to individuals in the other pattern ( P < 0.05 for both). Conclusions: These data suggest that a dietary pattern more consistent with dietary guidelines may have a beneficial impact on physical and mental fatigue in the oldest old. Funding Sources: United States Department of Agriculture, Agricultural Research Service agreement 8050–51530-012–01A. Supporting Tables, Images and/or Graphs: